Videoengravings: Hybrid video processes - Moreira, Mateus Dutra Brandão; Garrossini, Daniela Fávaro (Revista do Colóquio, 2023)
This article contemplates reflections and practices on the concepts of video as a hybrid process, of media interconnection that starts to be valued in its interface character, as a system of connections between artistic practices. The meeting between engraving and video is presented, with the aim of investigating the transformations that occurred in the hybridization process between different elements of Goya's Los Caprichos engravings, in the author's video arts. Through a creative process, the experiments of three authorial works called Sonho 1, Sonho 2 and Sonho 3 are presented, which seek to analyze these concepts, their openings, dialogues and hybridity.